2021
DOI: 10.1002/mrm.28828
|View full text |Cite
|
Sign up to set email alerts
|

Local perturbation responses and checkerboard tests: Characterization tools for nonlinear MRI methods

Abstract: Purpose: Modern methods for MR image reconstruction, denoising, and parameter mapping are becoming increasingly nonlinear, black-box, and at risk of "hallucination." These trends mean that traditional tools for judging confidence in an image (visual quality assessment, point-spread functions (PSFs), g-factor maps, etc.) are less helpful than before. This paper describes and evaluates an approach that can help with assessing confidence in images produced by arbitrary nonlinear methods. Theory and Methods: We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…For the latter, prior work found that NORDIC had no impact on the functional point spread of the BOLD signal (Vizioli et al, 2021). To further validate these results we performed an initial evaluation using the local perturbation response (LPR) method (Chan and Haldar, 2021) and did not observe any image blurring on a checkerboard perturbation (Supplemental Figure S9, S11).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For the latter, prior work found that NORDIC had no impact on the functional point spread of the BOLD signal (Vizioli et al, 2021). To further validate these results we performed an initial evaluation using the local perturbation response (LPR) method (Chan and Haldar, 2021) and did not observe any image blurring on a checkerboard perturbation (Supplemental Figure S9, S11).…”
Section: Discussionmentioning
confidence: 94%
“…For the latter, prior work found that NORDIC had no impact on the functional point spread of the BOLD signal (Vizioli et al, 2021). To further validate these results we performed an initial evaluation using the local perturbation response (LPR) method (Chan and Haldar, 2021) and were able to recover the injected synthetic sparse signal, though sufficiently low intensity perturbations (i.e. below or near thermal noise level) were not perfectly recovered (See Supplement, Figures S8, S13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current evaluative metrics directly correspond to what were used in the Proceedings of the National Academy of Sciences ( PNAS ) study. 15 However, it will be valuable and interesting to assess the clinical influence of reconstructed results using other advanced assessment methods (local perturbation responses 54 and Frechet inception distance 55 ). In addition, the used deep tomographic networks are based on CNN architectures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the learned representation currently serves as a voxel-wise constraint, it can introduce timedependent bias into the final reconstruction thus frequencydependent spatial resolution. While the traditional metrics (like FWHM of point spread functions) are not sufficient to analyze such resolution effects with the nonlinearity of neural networks, a more careful spatial resolution analysis of the denoised reconstruction should be conducted in future research (e.g., using new analysis tools such as [59]).…”
Section: Discussionmentioning
confidence: 99%